L'expressió de les hores en català: anàlisi contrastiva - Torres i Vilatarsana, Marta (Caplletra. Revista Internacional de Filologia, 2001)
What time is it? Prefaced by this question, this paper investigates a number of ways to express the time in Catalan from a dialectal and pragmatic perspectiva. In this article, all dialectal varieties of the two main ways to tell the time (one based on the next hour, i.e. “one quarter of nine”, and the other based on the current hour, i.e. “eight and a quarter”) from the data from 190 locations surveyed for the Atles Lingüístic del Domini Català are described. The results of this analysis are compared to descriptive and normative proposals: grammars, style manuals, dictionaries, and other information sources. Finally, we give an account of the decline or the success of the two ways to tell the time in Catalan dialects by comparing them with the common ways to tell the time in neighbor languages, and by identifying aspects of linguistic economy and the degree of similarity between the ways, and by studying their sociolinguistic development.